RP-HPLC Method for the Estimation of Nebivolol in Bulk and Pharmaceutical Dosage Form - Raja Rajeswari, K.; Sankar, G.G.; Rao, A.L.; Raju, D.B.; Seshagiri Rao, J.V.L.N. (Asian Journal of Chemistry, 2016)
A rapid and sensitive high performance liquid chromatographic method was developed for the estimation of nebivolol in bulk and pharmaceutical dosage form. Nebivolol was chromatographed on a reverse phase C18 column in a mobile phase consisting of acetonitrile and 30 mM KH2PO4 buffer (pH 3.1 adjusted with o-H3PO4) in the ratio of 55 : 45 (v/v). the mobile phase was pumped at a flow rate of 0.8 mL/min and the eluents were monitored at 286 nm. The calibration curve was linear in the range of 0.5-50 μg/mL. The intra- and inter-day variation was found to be less than 1% showing high precision of the assay method. The mean recovery of the drug from the solution containing 4 μg/mL was 100.81 ± 0.075 indicating high accuracy of the proposed method. Due to its simplicity, rapidness, high precision and accuracy, the proposed HPLC method may be used for determining nebivolol in bulk and pharmaceutical dosage forms.